A lesion-mimic mutant of Catharanthus roseus accumulates the opioid agonist, akuammicine. (November 2022) - Li, Fanfan; Bordeleau, Stephen; Kim, Kyung Hee; Turcotte, Jonathan; Davis, Benjamin; Liu, Lan; Bayen, Stéphane; De Luca, Vincenzo; Dastmalchi, Mehran
Abstract: Catharanthus roseus is a medicinal plant that produces an abundance of monoterpenoid indole alkaloids (MIAs), notably including the anticancer compounds vinblastine and vincristine. While the canonical pathway leading to these drugs has been resolved, the regulatory and catalytic mechanisms controlling many lateral branches of MIA biosynthesis remain largely unknown. Here, we describe an ethyl methanesulfonate (EMS) C. roseus mutant (M2 -117523) that accumulates high levels of MIAs. The mutant exhibited stunted growth, partially chlorotic leaves, with deficiencies in chlorophyll biosynthesis, and a lesion-mimic phenotype. The lesions were sporadic and spontaneous, appearing after the first true bifoliate and continuing throughout development. The lesions are also the site of high concentrations of akuammicine, a minor constituent of wild type C. roseus leaves. In addition to akuammicine, the lesions were enriched in 25 other MIAs, resulting, in part, from a higher metabolic flux through the pathway. The unique metabolic shift was associated with significant upregulation of biosynthetic and regulatory genes involved in the MIA pathway, including the transcription factors WRKY1, CrMYC2, and ORCA2, and the biosynthetic genes STR, GO, and Redox1 . Following the lesion-mimic mutant (LMM) phenotype, the accumulation of akuammicine is jasmonate (JA)-inducible, suggesting a role in plant defence response. Akuammicine is medicinally significant, as a weak opioid agonist, with a preference for the κ -opioid receptor, and a potential anti-diabetic. Further study of akuammicine biosynthesis and regulation can guide plant and heterologous engineering for medicinal uses. Graphical abstract: A Catharanthus roseus lesion-mimic mutant accumulates the opioid agonist, akuammicine, along with 25 other MIAs enriched exclusively in its lesions. Image 1 Highlights: Catharanthus roseus mutant accumulates monoterpenoid indole alkaloids (MIAs). Mutant displays lesion-mimic phenotype with chlorosis and spontaneous lesions. Significant upregulation of MIA regulatory and biosynthetic genes. Lesions accumulate akuammicine and are enriched with 25 other MIAs. Akuammicine is jasmonate-inducible, with a potential role in plant defense.